Youth Homelessness: The Impact of Supportive Relationships on Recovery - Gasior, Sara (2015)
Abstract AIM: To test a model based on Peplau’s theory of Interpersonal Relations, which examines the influence of a network of service providers, perceptions of social supports and perceptions of family relations on a homeless youth’s perceptions of recovery. BACKGROUND: Homeless youth comprise an extremely disenfranchised group and have been recognized as one of the fastest growing sub-groups within the homeless population. Homeless youth face impaired access to health and social services. They are often left unsupported and lack social and familial support or relationships with service providers. Homeless youth left unsupported frequently sink into a cycle of homelessness that extends into adulthood. METHODS: This study is a secondary analysis and used a subsample of the original Youth Matters study. A predictive, non-experimental design was used to test the relationship of a network of service providers, perceived social support and perceived family relations on perceptions of recovery in the homeless youth population. A sample of homeless youth (n= 187) in Ontario, Canada were interviewed at six month intervals over a 2.5 year period. Hierarchical multiple regression analysis was used. RESULTS: Network of service providers, perceived social supports and perceived family relations explained 21.8% of the variance in homeless youth perceptions of recovery. Perceived social support and family relations were significantly, positively correlated to perceptions of recovery. Network of service providers was not significantly correlated to perceptions of recovery. CONCLUSIONS: The findings suggest that stronger social supports and family relations may contribute to increased perceptions of recovery among homeless youth. IMPLICATIONS FOR FUTURE PRACTICE: Health and social service providers must understand the importance of implementing interventions that foster supportive relationships and networks of support in the homeless youth population. KEYWORDS: homeless; youth; recovery; social support; family; service provide